2015
DOI: 10.1016/j.eurpsy.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Parental Psychosis and Early Motor Development and the Risk of Schizophrenia in a General Population Birth Cohort

Abstract: BackgroundDelayed motor development in infancy and family history of psychosis are both associated with increased risk of schizophrenia, but their interaction is largely unstudied.AimTo investigate the association of the age of achieving motor milestones and parental psychosis and their interaction in respect to risk of schizophrenia.MethodsWe used data from the general population-based prospective Northern Finland Birth Cohort 1966 (n = 10,283). Developmental information of the cohort members was gathered dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…Early parenthood-related and developmental risk factors of schizophrenia (Keskinen et al, 2013;Keskinen et al, 2015) did not predict later outcomes of illness, with the exception of young maternal age. Based on our study, the prognosis of SSD may not be predetermined in early development, and this highlights even more the importance of effective, individualized treatments.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Early parenthood-related and developmental risk factors of schizophrenia (Keskinen et al, 2013;Keskinen et al, 2015) did not predict later outcomes of illness, with the exception of young maternal age. Based on our study, the prognosis of SSD may not be predetermined in early development, and this highlights even more the importance of effective, individualized treatments.…”
Section: Discussionmentioning
confidence: 85%
“…Early parenthood-related and developmental factors and their classifications were based on earlier literature to present factors that increase the risk of schizophrenia (Keskinen et al, 2013;Keskinen et al, 2015).…”
Section: Predictorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Small HC was related to an increased risk of later schizophrenia, independent of other factors (Cantor-Graae et al, 1998; Hultman et al, 1997) though other studies found no association, or relationships that were restricted to females (Wahlbeck et al, 2001; Welham et al, 2009). However, in contrast to other indices of development which delineate trajectories, including developmental milestones, neurocognition, and behavior prior to schizophrenia onset (Cannon et al, 1997; Isohanni et al, 2004; Keskinen et al, 2015; Khandaker et al, 2011), the pattern of HC growth among pre-schizophrenia cases following birth has not been well investigated because those studies utilized measures of HC that were isolated to birth. Growth trajectory of HC can more optimally be studied by examining growth velocity, which is defined as the rate of change in HC per unit change in time.…”
Section: Introductionmentioning
confidence: 99%